Biochemical Characterization and Phytochemical Analysis of Different Buckwheat Germplasm in Mid Hill of Sikkim - Das, Shaon Kumar; Yadav, Ashish; Prasad, Sita Kumari (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted during November–February of 2021–2022 and 2022–2023 at ICAR RC for NEH Region, Sikkim Centre, Gangtok, Sikkim, India for biochemical characterization, mineral and phytochemical contents of different buckwheat germplasm following standard analysis protocol. The results revealed that accession along with the variety were found to be superior for the desirable nutritional quality parameters in comparison with local variety Titey. The protein content was highest in Titey (11.2%) followed by Shimla B-1 (11.1%) and lowest in IC49671 and IC108510 (10.4%). Significant variation was estimated for tryptophan content for various genotypes ranges from 66.3 to 76.9 mg g-1 N. The crude fibre content showed the range of variation from 3.71 to 4.78% in dry mature grains of tartary buckwheat %. Maximum nitrogen free content was recorded in IC108518 (76.97%) followed by IC202268 (75.37%) and lowest was found in IC36805 (71.41%). Maximum Fe content was found in genotype IC108518 (3.50) followed by IC109549 (3.49) and lowest was recorded in genotype IC49671 (2.50 mg 100 g-1). Similarly, total phenol content ranged from 378.41 to 652.71 mg GAE 100 g-1 with an average content of 518.68 mg GAE 100 g-1. Therefore, development and utilization of such functional foods will not only improve the nutritional status of the poor people but also helps those suffering from degenerative diseases. Wide variations among genotypes for quality attributes have shown ample potential to be exploited for further improvement of desirable quality attributes and other properties. This is the first-time study for biochemical and phytochemical analysis of buckwheat in Sikkim condition.